High-hardness, bend-resistant, VOC-free, electron beam-cured coating for decorative paper and method of making same
Patent Information
- Application Number
- CN202611245236.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-17
- Publication Date
- 2026-10-16
AI Technical Summary
[0006]有鉴于此,本发明的目的在于提出一种装饰纸用高硬度耐弯折无VOC电子束固化涂料及其制备方法,以解决现有装饰纸用电子束固化涂料难以兼顾高硬度与耐弯折性,并易出现施工黏度升高、弯折白化及涂层脱落,难以适应连续涂布和饰面加工的问题
[0034] This invention employs bi-arm modified cellulose nanofibers as a reactive reinforcing component in coatings, grafting polycaprolactone diacrylate long arms and methacrylamide short arms onto the cellulose nanofiber skeleton. The cellulose nanofiber skeleton provides surface support for the cured film, while the polycaprolactone segments alleviate localized stress concentration in the bending areas of the decorative paper, thereby reducing coating whitening, cracking, and interfacial delamination.
Smart Images

Figure CN122918873A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of coating technology, specifically to a high-hardness, bend-resistant, VOC-free electron beam-cured coating for decorative paper and its preparation method. Background Technology
[0002] Decorative paper is widely used on furniture veneers, engineered flooring, interior wall panels, and other engineered wood surfaces. Its printed surface typically requires a transparent coating to protect the printed design and improve surface hardness, abrasion resistance, gloss retention, and lifespan. Therefore, the coating for decorative paper not only needs to form a dense, continuous cured film but also needs to be adaptable to subsequent winding, cutting, bending, laminating, and hot-pressing processes.
[0003] Existing solvent-based or UV-cured coatings typically rely on volatile organic solvents, reactive diluents, or photoinitiators to adjust their application and curing properties, which can easily lead to the release of volatiles, residual odors, or migration of small molecules. Electron beam-cured coatings can form films rapidly without the use of photoinitiators, but existing formulations often achieve high hardness by increasing the content of multifunctional monomers and crosslinking density. The resulting coatings are prone to whitening, cracking, or decreased adhesion at bending points due to excessive rigidity.
[0004] The decorative base paper itself is relatively thin and has fiber orientation, and there are differences in modulus and deformation between the coating and the paper base. While adding flexible resin can improve bending resistance, it may reduce surface hardness, abrasion resistance, and curing integrity. Adding inorganic fillers or cellulose materials can easily cause increased coating viscosity, particle agglomeration, and insufficient interfacial bonding, affecting coating uniformity and the continuity of the electron beam curing network.
[0005] Therefore, the main difficulty faced by existing electron beam curing coatings for decorative paper is that it is difficult to maintain suitable application viscosity, high hardness, abrasion resistance and repeated bending integrity without the addition of volatile organic solvents, which limits their application in continuous high-speed coating and flexible decorative paper processing. Summary of the Invention
[0006] In view of this, the purpose of this invention is to propose a high-hardness, bend-resistant, VOC-free electron beam curing coating for decorative paper and its preparation method, so as to solve the problems that existing electron beam curing coatings for decorative paper are difficult to balance high hardness and bend resistance, and are prone to increased application viscosity, whitening upon bending and coating peeling, making them unsuitable for continuous coating and finishing processes.
[0007] To achieve the above objectives, the present invention provides a high-hardness, bend-resistant, VOC-free electron beam-cured coating for decorative paper, comprising the following components by weight:
[0008] 100.00~110.00 parts aliphatic polyester polyurethane diacrylate;
[0009] 35.00~40.00 parts of isoborneol acrylate;
[0010] 10.00~12.50 parts of triethoxylated trimethylolpropane triacrylate;
[0011] 1.50~3.00 parts of bi-arm modified cellulose nanofibers;
[0012] 0.30~0.45 parts acrylic functional silicone surface additive;
[0013] The preparation steps of the double-arm modified cellulose nanofibers are as follows:
[0014] (1) ε-caprolactone is subjected to ring-opening polymerization initiated by N-tert-butoxycarbonylethanolamine to obtain N-tert-butoxycarbonyl-protected amino-terminated polycaprolactone hydroxy oligomer; the amino-terminated polycaprolactone hydroxy oligomer is reacted with diacrylate isocyanate, and then subjected to acid deprotection and salt formation treatment to separate amino-terminated polycaprolactone diacrylate hydrochloride.
[0015] (2) 2,2,6,6-Tetramethylpiperidine-1-oxygen radical oxidized cellulose nanofibers were dispersed in a buffer solution, activated with 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide, and amino-terminated polycaprolactone diacrylate hydrochloride was added to obtain cellulose nanofibers grafted with long arms of polycaprolactone diacrylate.
[0016] (3) The product obtained in step (2) is separated and washed, redispersed in buffer solution, activated with 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide, and after reaction with N-(2-aminoethyl)methacrylamide hydrochloride, the double-arm modified cellulose nanofibers are obtained after separation and purification.
[0017] Preferably, the ratio of N-tert-butoxycarbonylethanolamine, ε-caprolactone, and diacrylate isocyanate is 10.40-15.60g:36.80-55.20g:15.60-23.40g.
[0018] More preferably, the ratio of N-tert-butoxycarbonylethanolamine, ε-caprolactone, and diacrylate isocyanate is 13g:46g:19.50g.
[0019] Preferably, the ratio of the 2,2,6,6-tetramethylpiperidine-1-oxygen radical oxidized cellulose nanofibers to the amino-terminated polycaprolactone diacrylate hydrochloride / N-(2-aminoethyl)methacrylamide hydrochloride is 10g:3.80~4.60g:0.45~0.60g.
[0020] Preferably, step (1) specifically involves mixing N-tert-butoxycarbonylethanolamine, ε-caprolactone and stannous octoate, reacting them at 115°C for 6 hours under a nitrogen atmosphere, and then cooling them down to 60°C to obtain N-tert-butoxycarbonyl-protected amino-terminated polycaprolactone hydroxy oligomer.
[0021] Preferably, p-methoxyphenol and dibutyltin dilaurate are added to the N-tert-butoxycarbonyl-protected amino-terminated polycaprolactone hydroxy oligomer, followed by the addition of diacrylate isocyanate, and the reaction is continued at 60°C for 3 hours; then the temperature is lowered to 2°C, ethyl acetate hydrochloride solution is added dropwise, and the temperature is raised to 23°C and reacted for 2.5 hours.
[0022] Preferably, in step (2), 2,2,6,6-tetramethylpiperidine-1-oxygen radical oxidized cellulose nanofibers are added to 2-(N-morpholine) ethanesulfonic acid buffer, dispersed, and then 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, N-hydroxysuccinimide and p-methoxyphenol are added, and activated at 20~25℃ for 20~40 min.
[0023] Preferably, amino-terminated polycaprolactone diacrylate hydrochloride is added to the activated dispersion, and the pH of the system is adjusted to 6.8-7.2 with sodium bicarbonate. The reaction is carried out under nitrogen protection and light protection for 12-18 hours to obtain cellulose nanofibers grafted with the long arms of polycaprolactone diacrylate.
[0024] Preferably, the 2-(N-morpholine)ethanesulfonic acid buffer solution has a pH of 5.3-5.8 and a concentration of 50 mmol / L.
[0025] Preferably, in step (3), N-(2-aminoethyl)methacrylamide hydrochloride is added after activation, and the pH of the system is adjusted to 6.8~7.2 with sodium bicarbonate, and the reaction is carried out at 20~25°C in the dark for 8~12 hours.
[0026] Preferably, in step (3), the freeze drying is carried out at -55~-45℃ and 10~30Pa for 24~36h.
[0027] This invention also provides a method for preparing a high-hardness, bend-resistant, VOC-free electron beam-cured coating for decorative paper, comprising the following steps:
[0028] Isoborneol acrylate, triethoxylated trimethylolpropane triacrylate and biarm modified cellulose nanofibers were dispersed, and then aliphatic polyester polyurethane diacrylate and acrylic functional organosilicon surface additives were added for mixing and degassing to obtain an electron beam cured coating.
[0029] Preferably, the dispersion rotation speed is 7500~8000 r / min and the dispersion time is 20~25 min.
[0030] Preferably, the degassing is carried out under conditions of -0.080 to -0.070 MPa for 8 to 10 minutes.
[0031] Furthermore, the present invention also provides a decorative paper, comprising applying the electron beam curable coating to the printing surface of a printing decorative base paper, wherein the coating amount is 8.00~11.50 g / m². 2 The coated decorative paper is then sent to a nitrogen-protected electron beam curing zone for single-pass electron beam irradiation curing to obtain decorative paper.
[0032] Preferably, the oxygen content in the electron beam curing zone is 300~450ppm, the electron beam accelerating voltage is 100~125kV, the absorbed dose is 35~45kGy, and the paper feed speed is 20~40m / min.
[0033] The beneficial effects of this invention:
[0034] This invention employs bi-arm modified cellulose nanofibers as a reactive reinforcing component in coatings, grafting polycaprolactone diacrylate long arms and methacrylamide short arms onto the cellulose nanofiber skeleton. The cellulose nanofiber skeleton provides surface support for the cured film, while the polycaprolactone segments alleviate localized stress concentration in the bending areas of the decorative paper, thereby reducing coating whitening, cracking, and interfacial delamination.
[0035] The acrylic groups at the distal end of the long arm of polycaprolactone and the polymerizable groups in the short arm of methacrylamide can participate in the formation of the coating curing network during electron beam irradiation, transforming cellulose nanofibers from ordinary filler materials into reactive nodes in the curing network. This is beneficial for improving the gel integrity, abrasion resistance, and adhesion stability of the coating after bending.
[0036] Aliphatic polyester-type polyurethane diacrylate provides a continuous film-forming matrix with certain deformability. Isoborneol acrylate and triethoxylated trimethylolpropane triacrylate work together to regulate the coating's application flowability and curing crosslinking degree, achieving a reasonable balance between surface hardness and flexural resistance. Acrylic functional silicone surface additives can also improve coating leveling and the surface condition of the cured film.
[0037] Dispersing the double-arm modified cellulose nanofibers before adding them to the main resin can reduce the tendency of unmodified fibers to agglomerate in the acrylate system, avoid component migration and interface separation caused by simple physical mixing, and enable the coating to form a more uniform reinforced structure while maintaining coatability.
[0038] The electron beam curing coating of the present invention does not actively add volatile organic solvents and completes single electron beam irradiation curing under nitrogen protection. It can reduce solvent evaporation and photoinitiator residue in traditional solvent-based or photocuring coatings. It is suitable for continuous coating of printing and decorative base paper and can be used on the surface of furniture veneer panels, reinforced flooring and interior decorative panels.
[0039] Compared with existing decorative paper coatings that mainly rely on increasing crosslinking density to obtain hardness, this invention utilizes double-arm modified cellulose nanofibers to participate in the electron beam curing network, which improves bending integrity and paper surface adhesion while maintaining surface hardness and abrasion resistance, and reduces the use of volatile organic solvents and photoinitiators. It is suitable for continuous coating of decorative paper and subsequent lamination, cutting and bending processes. Attached Figure Description
[0040] To more clearly illustrate the technical solutions in this invention or the prior art, the accompanying drawings used in the description of the embodiments or the prior art will be briefly introduced below.
[0041] Figure 1 This is a process flow diagram for preparing the electron beam cured coating and its decorative paper according to the present invention.
[0042] Figure 2 The uncured coatings obtained in each embodiment and comparative example were cured for 1000 seconds. -1 Apparent viscosity plot at shear rate.
[0043] Figure 3 The graph shows the whitening value of the fold lines of the electron beam-cured decorative paper obtained in each embodiment and comparative example after 100 bends.
[0044] Figure 4 The graph shows the 60° gloss retention rate of the electron beam cured decorative paper obtained in each embodiment and comparative example after 500 rpm abrasion resistance test.
[0045] Figure 5 Fourier transform infrared spectra of the original TEMPO oxidized cellulose nanofiber dry powder, the cellulose nanofibers with only the long arms of polycaprolactone diacrylate grafted in Example 5, and the cellulose nanofibers with moderate grafting degree and two arms modified by preparation example 3. Detailed Implementation
[0046] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments.
[0047] TEMPO oxidized cellulose nanofibers: TOCNF dry powder from Nanjing Tianlu Nanotechnology Co., Ltd.; carboxyl content 1.45~1.55mmol / g (conductivity titration); moisture content ≤5.0%; ash content ≤1.0%; dry basis cellulose content ≥94.0%.
[0048] Preparation Example 1: Preparation of amino-terminated polycaprolactone diacrylate hydrochloride
[0049] Step (1): Add 13.00 g of N-Boc-ethanolamine, 46.00 g of ε-caprolactone, and 80 mg of stannous octoate to a reactor equipped with a mechanical stirrer, thermometer, and nitrogen inlet. Stir at 150 r / min and purge with nitrogen for 20 min. Raise the temperature to 115 °C and maintain it for 6 h from the point where the material temperature reaches 115 °C. Cool the material to 60 °C to obtain amino-terminated polycaprolactone hydroxyl oligomer.
[0050] Step (2): Add 40 mg of p-methoxyphenol and 35 mg of dibutyltin dilaurate to the material obtained in step (1), and stir at 180 r / min for 10 min at 60 °C; add 19.50 g of diacrylate isocyanate, and continue to maintain at 60 °C for 3 h. Cool the material to 2 °C, and add 30.0 mL of 4 mol / L ethyl acetate hydrochloride solution dropwise over 30 min. After the addition is completed, raise the temperature to 23 °C and maintain it for 2.5 h.
[0051] Step (3): Under stirring at 300 r / min, the reaction solution obtained in step (2) was added dropwise to 1600 mL of methyl tert-butyl ether over a period of 25 min. After filtration, the solution was washed three times with 200 mL of methyl tert-butyl ether and dried under reduced pressure at 33 °C and 3.0 kPa for 10 h to obtain 67.40 g of amino-terminated polycaprolactone diacrylate hydrochloride. The amine value of the obtained product was 59.2 mg KOH / g, and the acrylate double bond equivalent was 482 g / mol.
[0052] Preparation Example 2: Preparation of Low-Grafting-Degree Bilateral Modified Cellulose Nanofibers
[0053] Step (1): 10.00 g of TEMPO oxidized cellulose nanofibers were added to 900 mL of 50 mmol / L 2-(N-morpholine) ethanesulfonic acid buffer at pH 5.3 and dispersed at 6000 r / min for 10 min. 850 mg of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, 500 mg of N-hydroxysuccinimide, and 20 mg of p-methoxyphenol were added, and the mixture was kept at 20 °C for 20 min. 3.80 g of amino-terminated polycaprolactone diacrylate hydrochloride and 350 mg of sodium bicarbonate obtained in Preparation Example 1 were added, and the pH was adjusted to 6.8. The mixture was kept under nitrogen protection and in the dark for 12 h.
[0054] Step (2): Centrifuge the product obtained in step (1) at 8000 r / min for 10 min, wash twice with 200 mL of deionized water, and then wash twice with 200 mL of 50% (volume fraction) ethanol aqueous solution. Disperse the washed solid in 800 mL of 50 mmol / L 2-(N-morpholine) ethanesulfonic acid buffer at pH 5.3, add 550 mg of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, 330 mg of N-hydroxysuccinimide, and 20 mg of p-methoxyphenol, and keep at 20 °C for 20 min. Add 450 mg of N-(2-aminoethyl)methacrylamide hydrochloride and 230 mg of sodium bicarbonate, adjust the pH to 6.8, and keep at 20 °C in the dark for 8 h.
[0055] Step (3): The product obtained in step (2) was centrifuged at 8000 r / min for 10 min, washed twice each with 200 mL of deionized water, 200 mL of 50% (volume fraction) ethanol aqueous solution, and 200 mL of tert-butanol, and then freeze-dried at -55℃ and 10 Pa for 24 h to obtain 11.39 g of low-grafted double-arm modified cellulose nanofibers. The residual carboxyl content of the obtained modified fibers was 1.19 mmol / g, and the total nitrogen content was 0.64%.
[0056] Preparation Example 3: Preparation of moderately grafted double-arm modified cellulose nanofibers
[0057] Step (1): 10.00 g of TEMPO oxidized cellulose nanofibers were added to 1000 mL of 50 mmol / L 2-(N-morpholine) ethanesulfonic acid buffer at pH 5.5 and dispersed at 7500 r / min for 15 min. 975 mg of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, 600 mg of N-hydroxysuccinimide, and 30 mg of p-methoxyphenol were added, and the mixture was kept at 23 °C for 30 min. 4.20 g of amino-terminated polycaprolactone diacrylate hydrochloride and 400 mg of sodium bicarbonate obtained in Preparation Example 1 were added, and the pH was adjusted to 7.0. The mixture was kept under nitrogen protection and in the dark for 15 h.
[0058] Step (2): Centrifuge the product obtained in step (1) at 9000 r / min for 12 min, wash twice with 200 mL of deionized water, and then wash twice with 200 mL of 50% (volume fraction) ethanol aqueous solution. Disperse the washed solid in 900 mL of 50 mmol / L 2-(N-morpholine) ethanesulfonic acid buffer at pH 5.5, add 650 mg of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, 395 mg of N-hydroxysuccinimide, and 30 mg of p-methoxyphenol, and keep at 23 °C for 30 min. Add 525 mg of N-(2-aminoethyl)methacrylamide hydrochloride and 275 mg of sodium bicarbonate, adjust the pH to 7.0, and keep at 23 °C in the dark for 10 h.
[0059] Step (3): The product obtained in step (2) was centrifuged at 9000 r / min for 12 min, washed twice each with 200 mL of deionized water, 200 mL of 50% (volume fraction) ethanol aqueous solution, and 200 mL of tert-butanol, and then freeze-dried at -50℃ and 20 Pa for 30 h to obtain 11.85 g of moderately grafted double-arm modified cellulose nanofibers. Blank recovery was performed using the same batch of TEMPO oxidized cellulose nanofibers following the same dispersion, centrifugation, washing, and freeze-drying process. The blank recovery dry weight was 9.76 g; the dry weight of the first grafted section after washing and freeze-drying was 11.45 g.
[0060] Preparation Example 4: Preparation of Highly Grafted Double-Arm Modified Cellulose Nanofibers
[0061] Step (1): 10.00 g of TEMPO oxidized cellulose nanofibers were added to 1100 mL of 50 mmol / L 2-(N-morpholine) ethanesulfonic acid buffer at pH 5.8 and dispersed at 9000 r / min for 20 min. 1100 mg of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, 700 mg of N-hydroxysuccinimide, and 40 mg of p-methoxyphenol were added, and the mixture was kept at 25 °C for 40 min. 4.60 g of amino-terminated polycaprolactone diacrylate hydrochloride and 450 mg of sodium bicarbonate obtained in Preparation Example 1 were added, and the pH was adjusted to 7.2. The mixture was kept under nitrogen protection and in the dark for 18 h.
[0062] Step (2): Centrifuge the product obtained in step (1) at 10000 r / min for 15 min, wash twice with 200 mL of deionized water, and then wash twice with 200 mL of 50% (volume fraction) ethanol aqueous solution. Disperse the washed solid in 1000 mL of 50 mmol / L 2-(N-morpholine) ethanesulfonic acid buffer at pH 5.8, add 750 mg of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, 460 mg of N-hydroxysuccinimide, and 40 mg of p-methoxyphenol, and keep at 25 °C for 40 min. Add 600 mg of N-(2-aminoethyl)methacrylamide hydrochloride and 320 mg of sodium bicarbonate, adjust the pH to 7.2, and keep at 25 °C in the dark for 12 h.
[0063] Step (3): The product obtained in step (2) was centrifuged at 10000 r / min for 15 min, washed twice each with 200 mL of deionized water, 200 mL of 50% (volume fraction) ethanol aqueous solution, and 200 mL of tert-butanol, and then freeze-dried at -45℃ and 30 Pa for 36 h to obtain 12.32 g of highly grafted double-arm modified cellulose nanofibers. The residual carboxyl content of the obtained modified fibers was 0.92 mmol / g, and the total nitrogen content was 1.05%.
[0064] Preparation Example 5: Cellulose nanofibers grafted only with the long arms of polycaprolactone diacrylate
[0065] Following step (1) of Preparation Example 3, the long-arm grafting was completed, and then centrifuged and washed under the conditions described at the beginning of step (2) of Preparation Example 3, without performing a second carboxyl activation and short-arm grafting. The washed solid was washed twice each with 200 mL of deionized water, 200 mL of 50% (volume fraction) ethanol aqueous solution, and 200 mL of tert-butanol, and then freeze-dried at -50℃ and 20 Pa for 30 h to obtain 11.45 g of cellulose nanofibers grafted only with polycaprolactone diacrylate long arms. Calculated on a blank recovery dry basis, the mass fractions of the fiber backbone and the polycaprolactone diacrylate long arms in the product were 85.24% and 14.76%, respectively.
[0066] Preparation Example 6: Cellulose nanofibers grafted only with short arms of methacrylamide
[0067] 10.00 g of TEMPO oxidized cellulose nanofibers were added to 900 mL of 50 mmol / L 2-(N-morpholine) ethanesulfonic acid buffer (pH 5.5) and dispersed at 7500 rpm for 15 min. Then, 650 mg of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, 395 mg of N-hydroxysuccinimide, and 30 mg of p-methoxyphenol were added, and the mixture was kept at 23 °C for 30 min. Next, 525 mg of N-(2-aminoethyl)methacrylamide hydrochloride and 275 mg of sodium bicarbonate were added, the pH was adjusted to 7.0, and the mixture was kept at 23 °C in the dark for 10 h. The product was centrifuged at 9000 r / min for 12 min, washed twice each with 200 mL of deionized water, 200 mL of 50% (v / v) ethanol aqueous solution, and 200 mL of tert-butanol, and then freeze-dried at -50℃ and 20 Pa for 30 h to obtain 10.16 g of cellulose nanofibers grafted only with methacrylamide short arms. Calculated on a blank recovery dry basis, the mass fractions of the fiber backbone and methacrylamide short arms in the product were 96.06% and 3.94%, respectively.
[0068] Preparation Example 7: Monoacrylate-based long-arm control modified cellulose nanofibers
[0069] Step (1): Amino-terminated polycaprolactone hydroxyl oligomer was prepared according to step (1) of Preparation Example 1. Except that 19.50 g of diacrylate isocyanate was replaced with 11.50 g of ethyl isocyanate acrylate, the amino-terminated polycaprolactone acrylate hydrochloride was obtained by performing end-capping, deprotection, precipitation, washing and vacuum drying according to steps (2) and (3) of Preparation Example 1.
[0070] Step (2): Except for replacing 4.20g of amino-terminated polycaprolactone diacrylate hydrochloride in step (1) of Preparation Example 3 with 3.75g of amino-terminated polycaprolactone acrylate hydrochloride obtained in step (1), the two-stage grafting, washing and freeze-drying were completed according to the remaining raw materials, amounts and conditions of Preparation Example 3, to obtain 11.67g of modified cellulose nanofibers with monoacrylate long arms and methacrylamide short arms grafted together.
[0071] The printing decorative base paper used in this embodiment of the invention is a commercially available product from the same batch provided by a decorative base paper manufacturer or a decorative paper printing company, and the printing surface is not pre-coated with a UV or electron beam coating layer. The basis weight of this batch of base paper is 80 g / m³. 2 Thickness: 92μm; Initial moisture content: 5.2%; Bekk smoothness of printed surface: 260s; Cobb 60 water absorption: 24g / m³ 2 The printing ink has dried and there is no sticking to the paper.
[0072] Example 1: Using 1.50 g of the double-arm modified cellulose nanofibers obtained in Preparation Example 3, the following process was followed: 35.00 g of isoborneol acrylate, 12.50 g of triethoxylated trimethylolpropane triacrylate, and the specified amount of modified cellulose nanofibers were added to a dispersion container and dispersed at 7500 r / min for 20 min; 100.00 g of aliphatic polyester polyurethane diacrylate and 0.45 g of acrylic functionalized silicone surface additive were added and mixed at 650 r / min for 20 min, followed by degassing at -0.070 MPa for 8 min to obtain an electron beam-cured coating without added volatile organic solvents. The obtained coating was applied to the printing surface of a printing decorative base paper with a coating weight of 11.50 g / m². 2 The coated paper is fed into an electron beam curing zone protected by nitrogen and cured by single irradiation under conditions of 300 ppm oxygen content, 125 kV accelerating voltage, 35 kGy absorbed dose and 40 m / min paper feed speed to obtain electron beam cured decorative paper.
[0073] Example 2: Using 2.25 g of the double-arm modified cellulose nanofibers obtained in Example 3, the following process was followed: 35.00 g of isoborneol acrylate, 12.50 g of triethoxylated trimethylolpropane triacrylate, and the specified amount of modified cellulose nanofibers were added to a dispersion container and dispersed at 7500 r / min for 20 min; 100.00 g of aliphatic polyester polyurethane diacrylate and 0.45 g of acrylic functionalized silicone surface additive were added and mixed at 650 r / min for 20 min, followed by degassing at -0.070 MPa for 8 min to obtain an electron beam-cured coating without added volatile organic solvents. The obtained coating was applied to the printing surface of a decorative printing base paper with a coating weight of 11.50 g / m². 2 The coated paper is fed into an electron beam curing zone protected by nitrogen and cured by single irradiation under conditions of 300 ppm oxygen content, 125 kV accelerating voltage, 35 kGy absorbed dose and 40 m / min paper feed speed to obtain electron beam cured decorative paper.
[0074] Example 3: Using 3.00 g of the double-arm modified cellulose nanofibers obtained in Example 3, the following process was followed: 35.00 g of isoborneol acrylate, 12.50 g of triethoxylated trimethylolpropane triacrylate, and the specified amount of modified cellulose nanofibers were added to a dispersion container and dispersed at 7500 r / min for 20 min; 100.00 g of aliphatic polyester polyurethane diacrylate and 0.45 g of acrylic functionalized silicone surface additive were added and mixed at 650 r / min for 20 min, followed by degassing at -0.070 MPa for 8 min to obtain an electron beam-cured coating without added volatile organic solvents. The obtained coating was applied to the printing surface of a decorative printing base paper with a coating weight of 11.50 g / m². 2The coated paper is fed into an electron beam curing zone protected by nitrogen and cured by single irradiation under conditions of 300 ppm oxygen content, 125 kV accelerating voltage, 35 kGy absorbed dose and 40 m / min paper feed speed to obtain electron beam cured decorative paper.
[0075] Example 4: Using 2.25 g of the double-arm modified cellulose nanofibers obtained in Preparation Example 2, the following process was followed: 35.00 g of isoborneol acrylate, 12.50 g of triethoxylated trimethylolpropane triacrylate, and the specified amount of modified cellulose nanofibers were added to a dispersion container and dispersed at 7500 r / min for 20 min; 100.00 g of aliphatic polyester polyurethane diacrylate and 0.45 g of acrylic functionalized silicone surface additive were added and mixed at 650 r / min for 20 min, followed by degassing at -0.070 MPa for 8 min to obtain an electron beam-cured coating without added volatile organic solvents. The obtained coating was applied to the printing surface of a decorative printing base paper with a coating weight of 11.50 g / m². 2 The coated paper is fed into an electron beam curing zone protected by nitrogen and cured by single irradiation under conditions of 300 ppm oxygen content, 125 kV accelerating voltage, 35 kGy absorbed dose and 40 m / min paper feed speed to obtain electron beam cured decorative paper.
[0076] Example 5: Using 2.25 g of the double-arm modified cellulose nanofibers obtained in Example 4, the following process was followed: 35.00 g of isoborneol acrylate, 12.50 g of triethoxylated trimethylolpropane triacrylate, and the specified amount of modified cellulose nanofibers were added to a dispersion container and dispersed at 7500 r / min for 20 min; 100.00 g of aliphatic polyester polyurethane diacrylate and 0.45 g of acrylic functionalized silicone surface additive were added and mixed at 650 r / min for 20 min, followed by degassing at -0.070 MPa for 8 min to obtain an electron beam-cured coating without added volatile organic solvents. The obtained coating was applied to the printing surface of a decorative printing base paper with a coating weight of 11.50 g / m². 2 The coated paper is fed into an electron beam curing zone protected by nitrogen and cured by single irradiation under conditions of 300 ppm oxygen content, 125 kV accelerating voltage, 35 kGy absorbed dose and 40 m / min paper feed speed to obtain electron beam cured decorative paper.
[0077] Example 6: 40.00 g of isoborneol acrylate, 10.00 g of triethoxylated trimethylolpropane triacrylate, and 3.00 g of the moderately grafted double-arm modified cellulose nanofibers obtained in Preparation Example 3 were mixed and dispersed at 8000 r / min for 25 min. 110.00 g of aliphatic polyester-type polyurethane diacrylate and 0.30 g of acrylic functionalized silicone surface additive were added, and the mixture was stirred at 800 r / min for 25 min. The mixture was then degassed at -0.080 MPa for 10 min to obtain an electron beam-cured coating without added volatile organic solvents. The obtained coating was applied to the printing surface of a decorative printing base paper with a coating weight of 8.00 g / m². 2 Electron beam-cured decorative paper was obtained by single-irradiation curing under conditions of 450 ppm oxygen content, 100 kV accelerating voltage, 45 kGy absorbed dose, and 20 m / min paper feed speed.
[0078] Comparative Example 1: Except for replacing 2.25g of the double-arm modified cellulose nanofibers obtained in Preparation Example 3 of Example 2 with 1.853g of unmodified TEMPO oxidized cellulose nanofibers, and adjusting the amount of isoborneol acrylate from 35.00g to 35.397g, the other raw materials, amounts and preparation conditions were the same as in Example 2, and electron beam cured decorative paper was obtained.
[0079] Comparative Example 2: Except for replacing 2.25g of the double-arm modified cellulose nanofibers obtained in Preparation Example 3 of Example 2 with 1.853g of unmodified TEMPO oxidized cellulose nanofibers, 0.321g of amino-terminated polycaprolactone diacrylate hydrochloride and 0.076g of N-(2-aminoethyl)methacrylamide hydrochloride, the other raw materials, amounts and preparation conditions were the same as in Example 2, and electron beam cured decorative paper was obtained.
[0080] Comparative Example 3: Except for replacing 2.25g of the double-arm modified cellulose nanofibers obtained in Preparation Example 3 of Example 2 with 2.174g of cellulose nanofibers with only the long arms of polycaprolactone diacrylate grafted and 0.076g of N-(2-aminoethyl)methacrylamide hydrochloride obtained in Preparation Example 5, the other raw materials, amounts and preparation conditions were the same as in Example 2, and electron beam cured decorative paper was obtained.
[0081] Comparative Example 4: Except for replacing 2.25g of the double-arm modified cellulose nanofibers obtained in Preparation Example 3 of Example 2 with 1.929g of cellulose nanofibers with only short arms grafted with methacrylamide obtained in Preparation Example 6 and 0.321g of amino-terminated polycaprolactone diacrylate hydrochloride obtained in Preparation Example 1, the other raw materials, amounts and preparation conditions were the same as in Example 2, and electron beam cured decorative paper was obtained.
[0082] Comparative Example 5: Except for replacing 2.25g of the double-arm modified cellulose nanofibers obtained in Preparation Example 3 of Example 2 with 2.216g of the single-acrylic-based long-arm control modified cellulose nanofibers obtained in Preparation Example 7, adjusting the amount of isoborneol acrylate from 35.00g to 35.074g, and adjusting the amount of aliphatic polyester polyurethane diacrylate from 100.00g to 99.960g, the other raw materials, amounts, and preparation conditions were the same as in Example 2, resulting in electron beam-cured decorative paper. The amount adjustments ensured that the filament skeleton mass, number of long-arm molecules, short-arm mass, total number of acrylic double bonds, and total coating mass of Comparative Example 5 were consistent with those of Example 2.
[0083] Comparative Example 6: Except for adjusting the amount of double-arm modified cellulose nanofibers obtained in Preparation Example 3 of Example 2 from 2.25g to 1.20g, the other raw materials, amounts and preparation conditions were the same as in Example 2, and electron beam cured decorative paper was obtained.
[0084] Comparative Example 7: Except that the amount of the double-arm modified cellulose nanofibers obtained in Preparation Example 3 of Example 2 was adjusted from 2.25g to 3.30g, the other raw materials, amounts and preparation conditions were the same as in Example 2, and electron beam cured decorative paper was obtained.
[0085] Performance testing
[0086] Unless otherwise stated, the electron beam-cured decorative papers obtained in each embodiment and comparative example were conditioned for 24 hours at 23±1°C and 50±2% relative humidity before testing. All test samples were cut from an area more than 20 mm from the paper edge, with the cutting direction consistent with the coating orientation.
[0087] Residual carboxyl content and total nitrogen content of modified fibers: The residual carboxyl content was determined by conductivity titration. 50.0 mg of oven-dry sample was weighed, 10.0 mL of 0.01 mol / L hydrochloric acid was added, and the solution was diluted to 100 mL with deionized water. Titration was performed with 0.01 mol / L sodium hydroxide solution, and the carboxyl content was calculated based on the two inflection points of the conductivity curve. The total nitrogen content was determined using a combustion-based elemental analyzer. Each sample was measured in triplicate, and the average value was taken.
[0088] High shear apparent viscosity of coatings: The uncured coatings obtained from each sample were conditioned at 25°C for 30 min, and the shear rate was measured at 1000 s using a cone-plate rotational viscometer. -1 The apparent viscosity at that time was measured. The cone diameter was 50 mm, the cone angle was 1°, and the test gap was 0.05 mm; the pre-shear time was 30 s, and the average value was recorded over 10 consecutive s after stabilization. Each sample was measured in triplicate, and the results are shown in the figure. Figure 2 .
[0089] Corrected gel fraction: Independently cured films were prepared on silicone oil-treated polyethylene terephthalate release films according to the coating amount and electron beam conditions for each sample. 0.500 g of the cured film was weighed and recorded as m1; it was extracted with acetone at 23°C using a Soxhlet extraction method for 24 h, and dried at 60°C until the difference between two consecutive weighings was no greater than 0.5 mg, recorded as m2. The mass of insoluble cellulose fibers (m_f) in the sample was calculated based on the actual mass fraction of the insoluble cellulose component in each formulation. The corrected gel fraction was calculated as (m2-m_f) / (m1-m_f)×100%. Each sample was measured in triplicate.
[0090] Pencil hardness: Performed according to GB / T6739-2022. The coated paper is laid flat and fixed on a 3mm thick flat glass plate. A pencil is held at a 45° angle to the coated surface, and a load of 750g is applied. The pencil is then used to scratch 6.5mm at a speed of 0.5mm / s. Five parallel scratches are made for each hardness grade. The highest pencil hardness that does not produce the specified damage is reported.
[0091] Wear resistance mass loss: The rotary rubber grinding wheel method was used in accordance with GB / T1768-2006. The outer diameter of the sample was 100 mm, the diameter of the center hole was 6.5 mm, and the coating was facing upwards. A CS-10F grinding wheel was used, with a load of 250 g per wheel, a rotation speed of 60 r / min, and a running speed of 500 rpm. The samples were conditioned in the specified environment for 2 hours before and after the test and then weighed. The wear resistance mass loss was the difference in mass before and after the test. Each sample was measured in triplicate.
[0092] Bending endurance test: A MIT-type folding endurance tester was used, referring to GB / T457-2008. 15mm × 100mm test strips were cut longitudinally from the base paper, with the coating facing outwards. A tension of 4.90N was applied, and the strips were double-folded at 175 times / min. The machine was stopped and observed after every 10 folds. The test was stopped when a continuous coating crack longer than 2mm appeared under a 10x magnifying glass, and the number of double folds was recorded. Five samples were tested for each sample, and the average value was taken.
[0093] Adhesion grade after bending: Cut a 50mm × 100mm sample along the longitudinal direction of the base paper, and bend it back and forth 100 times around a 5mm diameter cylindrical mandrel with the coating facing outward; then, according to GB / T9286-2021, prepare a 6×6 grid with a spacing of 1mm on the coating surface, apply pressure-sensitive adhesive tape, and peel it off smoothly in a 180° direction after 60s. Three samples were tested for each sample, and the worst adhesion grade among the three samples was reported, with grade 0 being a completely flat cut edge and grade 5 being the most severe peeling.
[0094] Bending line whitening value: Following the adhesion level test procedure described above, 100 reciprocating bends were performed. The L* value of the central area of the bending line and the unbent area 10 mm from the bending line were measured using a D50 illuminator and 2° standard observer conditions. The bending line whitening value ΔL* is calculated as L* of the central area of the bending line minus L* of the unbent area. Five samples were measured for each sample, and the average value was taken. The results are shown below. Figure 3 .
[0095] 60° gloss retention rate after abrasion resistance: The 60° specular gloss was determined according to ISO 2813:2014. Initial gloss was measured at five fixed locations on each sample. Then, the sample was run for 500 revolutions under abrasion mass loss test conditions. After removing surface dust, the gloss was measured at the same locations after abrasion resistance. The gloss retention rate was calculated as 100% of the ratio of the average gloss after abrasion resistance to the average gloss of the initial gloss. Five samples were tested for each sample. The results are shown in [Figure number missing]. Figure 4 .
[0096] Volatile organic solvent residues: Ethyl acetate, methyl tert-butyl ether, ethanol, and tert-butanol were quantified using headspace gas chromatography. 1.000 g of uncured coating was weighed and placed in a 20 mL headspace vial. 5.00 mL of N,N-dimethylformamide and 0.50 mL of n-propanol internal standard solution were added. The vial was sealed and equilibrated at 80 °C for 30 min. 1.0 mL of headspace sample was injected. Calibration was performed using a polyethylene glycol capillary column and a flame ionization detector, with external and internal standard calibration. The sum of the mass fractions of the four solvents was taken as the volatile organic solvent residue. Each sample was measured in triplicate.
[0097] Fourier transform infrared spectroscopy: A comparison was made between the original TEMPO oxidized cellulose nanofiber powder, the cellulose nanofibers grafted only with polycaprolactone diacrylate long arms obtained in Example 5, and the moderately grafted double-arm modified cellulose nanofibers obtained in Example 3. Each sample was vacuum-dried at 60°C for 4 hours and then cooled in a desiccator for 30 minutes; spectroscopically pure potassium bromide was dried at 110°C for 3 hours. 1.50 mg of the sample and 150.0 mg of potassium bromide were weighed, mixed and ground for 3 minutes, placed in a 13 mm diameter tablet mold, and held under a 10t load for 2 minutes after vacuuming, using a blank potassium bromide sample from the same batch as the background. Transmission mode was used, with a test range of 4000–400 cm⁻¹. -1 The resolution is 4cm. -1 The scan was performed 32 times to compare changes in functional group combinations before and after long-arm grafting and after continued short-arm grafting.
[0098] Table 1. Core performance test results for each embodiment and comparative example.
[0099] Example 1 92.3 5H 16.4 110 0 496 Example 2 93.9 6H 13.0 128 0 469 Example 3 95.0 6H 11.7 96 1 530 Example 4 91.4 5H 15.8 91 1 575 Example 5 95.5 6H 11.3 104 0 606 Example 6 94.4 5H 14.0 143 0 503 Comparative Example 1 89.0 4H 23.1 38 3 143 Comparative Example 2 90.7 5H 19.0 56 2 675 Comparative Example 3 92.2 5H 18.2 101 1 536 Comparative Example 4 93.4 6H 17.0 44 2 612 Comparative Example 5 92.5 5H 17.9 81 1 576 Comparative Example 6 90.6 4H 20.5 80 1 471 Comparative Example 7 94.8 6H 15.8 61 2 549
[0100] Data Analysis: Examples 1 to 3 only varied the amount of the double-arm modified cellulose nanofibers obtained in Example 3. When the amount increased from 1.50 g to 2.25 g, the corrected gel fraction increased from 92.3% to 93.9%, the abrasion loss decreased from 16.4 mg to 13.0 mg, and the number of bends increased from 110 to 128. Further increasing the amount to 3.00 g reduced the abrasion loss to 11.7 mg, but the 1000s... -1 The apparent viscosity increased to 477 mPa·s, while the number of flexural cycles decreased to 96. This indicates that under the given formulation and curing conditions, a moderate amount of double-arm modified filaments can balance the formation of the cured network, abrasion resistance, application viscosity, and integrity under repeated flexural cycles.
[0101] Examples 4, 2, and 5 used bi-arm modified filaments with low, medium, and high grafting degrees, respectively. Example 4 had a corrected gel fraction of 91.4%, an abrasion mass loss of 15.8 mg, and a bending resistance of 91 cycles; Example 5 had corresponding values of 95.5%, 11.3 mg, and 104 cycles. The different grafting conditions simultaneously altered the grafting degree of both the long and short arms, thus only indicating that all three specific modification combinations are feasible. It also shows that increasing the grafting degree improves hardness and abrasion resistance while limiting bending performance; this change cannot be attributed solely to a single grafting parameter.
[0102] With compensation for the mass of the fiber skeleton and the total mass of the coating, Example 2 showed an increase in the corrected gel fraction from 89.0% to 93.9% compared to Comparative Example 1, abrasion mass loss from 23.1 mg to 13.0 mg, an increase in the number of flexural cycles from 38 to 128, and an improvement in the adhesion grade after bending from grade 3 to grade 0. This indicates that grafting the two types of polymerizable arms onto the fiber skeleton before adding the main resin helps reduce the tendency for aggregation and interfacial delamination caused by the direct addition of unmodified fibers.
[0103] Comparative Example 2 used a physical blend of the same filamentary skeleton, long-arm material, and short-arm material as Example 2. Its corrected gel fraction was 90.7%, abrasion loss was 19.0 mg, and bending resistance was 56 cycles, all of which failed to reach the 93.9%, 13.0 mg, and 128 cycles achieved in Example 2, respectively. This demonstrates that simple blending cannot replace the material relationship formed by pre-grafting two types of polymerizable arms onto the same filamentary skeleton.
[0104] Comparative Example 3 retained the long, flexible diacrylate arms without grafting short methacrylamide arms onto the filaments. Compared to Comparative Example 3, the corrected gel fraction of Example 2 increased from 92.2% to 93.9%, the abrasion mass loss decreased from 18.2 mg to 13.0 mg, and the adhesion grade after bending improved from grade 1 to grade 0. This indicates that grafting short polymerizable arms onto the filament surface is beneficial for increasing the fixation between the filament and the electron beam-cured network.
[0105] Comparative Example 4 grafted only short methacrylamide arms onto the filaments, while the long arms were added in a free state. Compared to Comparative Example 4, the bending resistance of Example 2 increased from 44 to 128 cycles, the whitening value at the bend line decreased from 4.17 to 0.88, and the adhesion grade after bending improved from level 2 to level 0. This indicates that after the long arms of polycaprolactone form a grafted connection with the filament skeleton, it helps to alleviate local strain concentration near the bend line and maintain the integrity of the coating's adhesion to the paper surface.
[0106] Comparative Example 5 used modified filaments containing only one acrylate group at the distal end of each long arm, and compensated for this by adjusting the amounts of isoborneol acrylate and polyurethane diacrylate to match the filament skeleton mass, number of long arm molecules, short arm mass, total number of double bonds, and total coating mass of Example 2. In Example 2, the corrected gel fraction increased from 92.5% to 93.9% compared to Comparative Example 5, the abrasion mass loss decreased from 17.9 mg to 13.0 mg, and the number of flexural cycles increased from 81 to 128. This indicates that placing two acrylate groups at the distal end of each long arm improves the chances of reactive bonding between the filament and the cured network, and is not solely due to an increase in the total number of double bonds in the system.
[0107] Example 1 and Comparative Example 6 used 1.50g and 1.20g of bi-arm modified filaments, respectively, with all other conditions being the same except for the dosage. When the dosage was reduced to 1.20g, the pencil hardness decreased from 5H to 4H, the abrasion resistance mass loss increased from 16.4mg to 20.5mg, and the adhesion grade after bending changed from level 0 to level 1, indicating that a dosage of 1.20g was insufficient to simultaneously establish the required surface bearing capacity and interfacial bonding in this system.
[0108] Example 3 and Comparative Example 7 used 3.00 g and 3.30 g of biarm modified fibers, respectively, with all other conditions being the same except for the dosage. When the dosage was increased to 3.30 g, the 1000 s... -1 The apparent viscosity increased from 477 mPa·s to 616 mPa·s, the abrasion mass loss increased from 11.7 mg to 15.8 mg, and the number of flexural cycles decreased from 96 to 61. This indicates that further increasing the amount of double-arm modified filaments will increase the viscosity of the coating during application and will limit the abrasion and flexural resistance properties to the dispersion state.
[0109] Example 6, under the combined conditions of a higher polyurethane diacrylate content, a lower trifunctional monomer content, a lower coating weight, and a higher absorbed dose, showed a pencil hardness of 5H, a flexural strength of 143 cycles, a post-flexural adhesion grade of 0, and a flexural whitening value of 0.79. These results demonstrate that another specific combination of the formulation and electron beam process can form a continuous cured layer and achieve a performance balance biased towards flexural strength, without attributing it separately to each simultaneously varying parameter.
[0110] Figure 5 All three samples retained 3400 cm.-1 Nearby hydroxyl band, 2900cm -1 The nearby CH zone and 1200~900cm -1 The cellulose backbone region. Compared to the original sample, the sample obtained in Preparation Example 5 has a 1722 cm² diameter. -1 The ester carbonyl band and 2944 cm -1 and 2872cm -1 Methylene band enhancement; the sample obtained in Preparation Example 3 also exhibited a 1548 cm⁻¹ -1 Amide II bands enhance the retention of the cellulose backbone and increase polycaprolactone ester segments and amide-containing structural units.
[0111] Those skilled in the art should understand that the discussion of any of the above embodiments is merely exemplary and is not intended to imply that the scope of the invention is limited to these examples; within the framework of the invention, the technical features of the above embodiments or different embodiments can also be combined, the steps can be implemented in any order, and there are many other variations of the different aspects of the invention as described above, which are not provided in the details for the sake of brevity.
Claims
1. A high-hardness, bend-resistant, VOC-free electron beam-cured coating for decorative paper, characterized in that, By mass parts, it includes the following components: 100.00~110.00 parts aliphatic polyester polyurethane diacrylate; 35.00~40.00 parts of isoborneol acrylate; 10.00~12.50 parts of triethoxylated trimethylolpropane triacrylate; 1.50~3.00 parts of bi-arm modified cellulose nanofibers; 0.30~0.45 parts acrylic functional silicone surface additive; The preparation steps of the double-arm modified cellulose nanofibers are as follows: (1) ε-caprolactone is subjected to ring-opening polymerization initiated by N-tert-butoxycarbonylethanolamine to obtain N-tert-butoxycarbonyl-protected amino-terminated polycaprolactone hydroxy oligomer; the amino-terminated polycaprolactone hydroxy oligomer is reacted with diacrylate isocyanate, and then subjected to acid deprotection and salt formation treatment to separate amino-terminated polycaprolactone diacrylate hydrochloride. (2) 2,2,6,6-Tetramethylpiperidine-1-oxygen radical oxidized cellulose nanofibers were dispersed in a buffer solution, activated with 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide, and amino-terminated polycaprolactone diacrylate hydrochloride was added to obtain cellulose nanofibers grafted with long arms of polycaprolactone diacrylate. (3) The product obtained in step (2) is separated and washed, redispersed in buffer solution, activated with 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide, and after reaction with N-(2-aminoethyl)methacrylamide hydrochloride, the double-arm modified cellulose nanofibers are obtained after separation and purification.
2. The electron beam curable coating according to claim 1, characterized in that, The ratio of N-tert-butoxycarbonylethanolamine, ε-caprolactone, and diacrylate isocyanate is 10.40-15.60g:36.80-55.20g:15.60-23.40g.
3. The electron beam curable coating according to claim 1, characterized in that, The ratio of the 2,2,6,6-tetramethylpiperidine-1-oxygen radical oxidized cellulose nanofibers to the amino-terminated polycaprolactone diacrylate hydrochloride / N-(2-aminoethyl)methacrylamide hydrochloride is 10g:3.80~4.60g:0.45~0.60g.
4. The electron beam curable coating according to claim 1, characterized in that, In step (2), 2,2,6,6-tetramethylpiperidine-1-oxygen radical oxidized cellulose nanofibers are added to 2-(N-morpholine) ethanesulfonic acid buffer, dispersed, and then 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, N-hydroxysuccinimide and p-methoxyphenol are added and activated at 20~25℃ for 20~40 min.
5. The electron beam curable coating according to claim 1, characterized in that, In step (2), amino-terminated polycaprolactone diacrylate hydrochloride is added to the activated dispersion, and the pH of the system is adjusted to 6.8-7.2 with sodium bicarbonate. The reaction is carried out under nitrogen protection and light protection for 12-18 hours to obtain cellulose nanofibers grafted with long arms of polycaprolactone diacrylate.
6. The electron beam curable coating according to claim 1, characterized in that, In step (3), N-(2-aminoethyl)methacrylamide hydrochloride is added after activation, and the pH of the system is adjusted to 6.8~7.2 with sodium bicarbonate, and the reaction is carried out at 20~25℃ in the dark for 8~12 hours.
7. A method for preparing a high-hardness, bend-resistant, VOC-free electron beam-cured coating for decorative paper according to any one of claims 1-6, characterized in that, Includes the following steps: Isoborneol acrylate, triethoxylated trimethylolpropane triacrylate and biarm modified cellulose nanofibers were dispersed, and then aliphatic polyester polyurethane diacrylate and acrylic functional organosilicon surface additives were added for mixing and degassing to obtain an electron beam cured coating.
8. The preparation method according to claim 7, characterized in that, The degassing was carried out under conditions of -0.080 to -0.070 MPa for 8 to 10 minutes.
9. The preparation method according to claim 7, characterized in that, The electron beam curable coating is applied to the printing surface of the decorative printing base paper, with a coating amount of 8.00~11.50 g / m². 2 The coated decorative paper is then sent to a nitrogen-protected electron beam curing zone for single-pass electron beam irradiation curing to obtain decorative paper.
10. The preparation method according to claim 9, characterized in that, The oxygen content in the electron beam curing zone is 300~450ppm, the electron beam accelerating voltage is 100~125kV, the absorbed dose is 35~45kGy, and the paper feed speed is 20~40m / min.